THE CONNECTION BETWEEN STUDENTS AT SMA HANG TUAH 5'S SELF ESTEEM AND SELF-CONTROL WITH NARCISSISTIC BEHAVIOR OF TIKTOK USERS - Indreswari, Oktavia; Fahmawati, Zaki Nur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the relationship between self-esteem and self-control with narcissistic behavior among TikTok users at Hang Tuah 5 Senior High School. Method: A quantitative correlational approach was employed, with saturated sampling involving 221 students. Data were collected through validated scales measuring narcissistic behavior, self-esteem, and self-control. Results: The findings revealed a positive correlation between self-esteem and narcissistic behavior, and a negative correlation between self-control and narcissistic behavior. Specifically, adolescents with higher self-esteem were more likely to exhibit narcissistic behavior due to their desire for attention and validation on social media, while those with lower self-control were less capable of regulating their behavior, leading to increased narcissistic tendencies. Novelty: This study provides new insights into the psychological dynamics influencing narcissistic behavior among adolescents in the digital era. It underscores the importance of enhancing self-control to mitigate excessive narcissism and offers a foundation for developing targeted psychological interventions for youth social media users.